2019
DOI: 10.1248/bpb.b19-00391
|View full text |Cite
|
Sign up to set email alerts
|

Artemether Attenuates the Progression of Non-small Cell Lung Cancer by Inducing Apoptosis, Cell Cycle Arrest and Promoting Cellular Senescence

Abstract: Lung cancer is the most common cause of cancer death, approximately 85% of which are non-small cell lung cancer (NSCLC). Here we found that artemether (ART), a natural derivative of artemisinin, significantly inhibits the proliferation of NSCLC cells in a dose-and time-dependent manner. We also demonstrated that high concentration of ART induces apoptosis in NSCLC cells through down-regulating the level of antiapoptotic protein B-cell lymphoma-2 (Bcl-2), cellular inhibitor of apoptosis protein 1 (cIAP1) and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…A previous study showed that BIRC2 expression regulates the apoptosis and survival of NSCLC cells: downregulating BIRC2 expression indirectly induces NSCLC cell apoptosis by preventing formation of the caspase-8–activating platform ( Yang and Wang, 2016 ; Jian et al, 2019 ). The overexpression of BIRC2 , regulated by Pellino-1, contributes to the oncogenesis of A549 and H1299 cells, which are both LUAD cell lines, and promotes cancer cell survival ( Jeon et al, 2016 ; Xv et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that BIRC2 expression regulates the apoptosis and survival of NSCLC cells: downregulating BIRC2 expression indirectly induces NSCLC cell apoptosis by preventing formation of the caspase-8–activating platform ( Yang and Wang, 2016 ; Jian et al, 2019 ). The overexpression of BIRC2 , regulated by Pellino-1, contributes to the oncogenesis of A549 and H1299 cells, which are both LUAD cell lines, and promotes cancer cell survival ( Jeon et al, 2016 ; Xv et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulating BIRC2 expression indirectly induces NSCLC cell apoptosis by preventing the formation of the caspase-8–activating platform ( Yang and Wang, 2016 ; Jian et al, 2019 ). Moreover, the positive rates of BIRC4 mRNA expression in pathological tissues of patients with NSCLC were reported to be significantly higher than those in the para-cancerous tissues ( De-Xuan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…BBR inhibits AP‐1 signaling pathway activity and reduces the binding of transcription factors to the CCND1 AP‐1 motifs, which is an essential mechanism for the action of berberine as a cyclin‐D1 regulator against human lung giant cell carcinoma 197 . Low concentrations of ART inhibit mRNA levels of cyclin‐related genes, including CDK2, CDK1, cyclin‐D1, CDK6, cyclin‐B1, and cyclin‐A2, which lead to cell cycle arrest of NSCLC cells 198 . Silybin inhibits human NSCLC cell growth by regulating the expression and function of key cell cycle regulators, reducing the protein levels of G1‐related CDK 2,4,6 and their corresponding cyclins‐D1 and D3, and inducing arrest of the cell cycle at G1 199 .…”
Section: Anti‐tumor Mechanismmentioning
confidence: 99%
“…The antitumor activity of ARTs involves multitargets and multipathways as mentioned above. Inducing cell cycle arrest is one of some common ones to inhibit proliferation of tumor cells (Jia et al, 2016;Chen J. et al, 2019), inhibit tumor cell invasion and metastasis (Rasheed et al, 2010;Weifeng et al, 2011), exerting antiangiogenic effects against tumor cells (Wei and Liu, 2017) and inducing cancer cell apoptosis (Jia et al, 2016;Chen J. et al, 2019). More recently, several new mechanisms on non-apoptotic cell death e.g.…”
Section: The Effects Of Arts On Cell Signaling Pathways and Modes Of mentioning
confidence: 99%